Molecular Weight and Solubility Studies of Some Novel Polyaniline Induced by Montmorillonite clay Called Maghnite-H+ (Algerian MMT) - Rahmouni, Abdelkader; Amine, Harrane; Mohammed, Belbachir (International Journal of Scientific World, 2013)
Aniline is well known to be polymerized by protonic acid such as chlorhydric acid (HCl?. The cationic polymerization of ANI was examined in the presence of Mag-H+ (eco-catalyst layered) powder in bulk at 0°C. In this paper, polyaniline (PANI)/Na+-maghnite (Mag) clay nanocomposite materials have been successfully prepared for the heterogeneous polymerization of aniline. The prepared samples were subsequently characterized by FTIR spectroscopy, 1H-NMR spectroscopy and gel permeation chromatography (GPC). It should be noted that the nanocomposite coating containing 1wt. %, 3wt. %, and 5wt. % of clay loading was found to exhibit an observable structure, physicochemical properties and controlled molecular weight. Oxidation states of PANI were found to influence the gel content molecular weight distribution,solubilite and conductivity of homopolymer produced, conformation and configuration of the polymer molecules.